2017
DOI: 10.1007/s00015-017-0266-3
|View full text |Cite
|
Sign up to set email alerts
|

Preserved organic matter in a fossil Ocean Continent Transition in the Alps: the example of Totalp, SE Switzerland

Abstract: Evidence from ultraslow spreading mid-ocean ridges and both fossil and present-day Ocean-Continent Transitions (OCT) demonstrates that mantle serpentinization resulting from the interaction of mantle rock and water during tectonic exhumation is widespread. Observations at white smokers in modern ocean settings suggest that methane produced by serpentinization can support methanotrophic bio-systems, which use methane as the only source of carbon. An important question is whether such bio-systems are more genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Based on the presence of biomarkers (e.g. pristane, phytane, squalane, hopanes, and steranes) or higher relative abundances of n-C 16 to n-C 20 alkanes, 26,54 amino acids, and long-chain n-alkanes 53 identified in the solvent-extracted fraction, they all concluded that the organic carbon was of biological origin, as supported by TOC isotopic analysis of the oceanic rocks. 25,28 However, biological contamination may have overprinted any possible abiotic geochemical signatures, 26 since these oceanic basement rocks have been affected by long-lived hydrothermal alteration and present-day microbial ecosystems.…”
Section: Bulk Rock Investigationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the presence of biomarkers (e.g. pristane, phytane, squalane, hopanes, and steranes) or higher relative abundances of n-C 16 to n-C 20 alkanes, 26,54 amino acids, and long-chain n-alkanes 53 identified in the solvent-extracted fraction, they all concluded that the organic carbon was of biological origin, as supported by TOC isotopic analysis of the oceanic rocks. 25,28 However, biological contamination may have overprinted any possible abiotic geochemical signatures, 26 since these oceanic basement rocks have been affected by long-lived hydrothermal alteration and present-day microbial ecosystems.…”
Section: Bulk Rock Investigationsmentioning
confidence: 97%
“…More recently, three studies characterized by bulk molecular approaches (1) serpentinized peridotites and gabbroic rocks recovered at the Atlantis Massif (30 N MAR) at both the Lost City hydrothermal field and Hole U1309D (Expeditions 304/305, Integrated Ocean Drilling Program (IODP)), 26 (2) peridotites from the Ashadze (12 58ʹN) and Logatchev hydrothermal sites along the MAR, 53 and (3) the fossil ocean-continent transition recorded in the Swiss Alps. 54 All of these studies used gas chromatography and/or gas chromatography-mass spectrometry. Based on the presence of biomarkers (e.g.…”
Section: Bulk Rock Investigationsmentioning
confidence: 99%
“…Water color can be observed with the naked eye (directly) or measured using the platinum cobalt scale (in PtCo units), comparing the color of the water sample and the standard color [20]. The difference in colour values obtained may be due to the presence of different amounts of organic substances or the geology of the stream [21].…”
Section: Figure 4 Relationship Between Ph Concentrationand River Dist...mentioning
confidence: 99%